Degradation of sulfapyridine antibiotics by chlorination in a pilot-scale water distribution system: kinetics, THMs, and DFT studies. Issue 10 (15th August 2022) - Ji, Jie; Shi, Changjie; Xu, Luo; Zhang, Kai; Zhang, YunShu; Li, Cong; Lichtfouse, Eric
Abstract : Sulfonamides (SAs) have been proved to damage organisms if the contact time last over the long term. Abstract : Sulfonamides (SAs) have been proved to damage organisms if the contact time last over the long term. Therefore, sulfapyridine (SPD), as typical one, was chosen as a target to be investigated. For the study, the degradation kinetic of SPD in the chlorination stage of a pilot-scale water distribution system (WDS) was studied. The result showed that the degradation of SPD simultaneously followed the first-order and pseudo second-order kinetic model. In the beakers tests or WDS, the reaction rate reaches maximum value when the pH is about 7. The degradation rate of SPD would be higher with the increase of water velocity in the WDS. Different pipe materials were studied and the degradation effect of SPD was in the following order: stainless-steel pipe > ductile iron pipe > polyethylene (PE) pipe. There was a significant increase in the content of trihalomethanes (THMs) when chlorination of tap water containing SPD in both the WDS and the beakers system were performed. The mechanism of this process was analyzed in combination with the intermediate products degraded by SPD in the process. In addition, density functional theory (DFT) calculations were performed to assist in the identification of 6 intermediates and possible degradation pathways.